The Strengths-Based Inclusive Theory of Work. (February 2019) - Owens, Rhea L.; Allan, Blake A.; Flores, Lisa Y.
This paper describes a new vocational theory—the strengths-based inclusive theory of work (S-BIT of Work). This theory addresses the ever-changing, dynamic nature of the world of work and integrates counseling psychology's core values of emphasizing vocational psychology, strengths-based perspectives, multiculturalism, and social justice. We aim to provide a holistic vocational theory to inform career and work counseling practice by increasing clinicians' cultural responsivity, promoting clients' strengths and optimal functioning, and addressing a variety of vocational challenges across developmental stages. This first article in the Major Contribution includes a discussion of the S-BIT of Work's core assumptions and theoretical propositions, research supporting the development of the S-BIT of Work, as well as future directions. The second and third articles in this Major Contribution discuss a model of fulfulling work, and the infusion of positive psychology and cultural responsivity in work counseling practice, respectively.